Development of Sparkol Videoscribe Interactive Video Learning Media Integrated with Case Method on Pancasila Material - Triyani, Triyani; Karliani, Eli; Lion, Eddy; Dotrimensi, Dotrimensi (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
This study aims to develop an interactive Sparkol VideoScribe learning video integrated with the case method in the Pancasilacourse, which will enable students to understand the Pancasila material better. The problem is the lack of interactive learning mediathat students can access, especially when learning Pancasila. This research uses the type of research development (Research andDevelopment) with the 4-D development model with the stages of defining, designing, developing and dissemination. Thedevelopment stages are integrated in the activities of 1) Integration of Pancasila material, namely the History of Pancasila Formulation, Pancasila as an Ethical System and Pancasila as the Basis for Science and Technology Development; 2) Integrating the material that has been developed into the Sparkol VideoScribe application; 3) Development of Sparkol VideoScribe Interactive Video integrated with Case Method; 4) Preparation of validation instruments and validation of Sparkol VideoScribe Interactive Video Integrated with Case Method by material experts and media experts; 5) Implementing videos that have beendeveloped to students while reflecting and evaluating; 6) Disseminating research products to students. The results of this studyare based on the results of material expert validation obtained a result of 85% with the category